Censored distraction and diversion inside China's great firewall - Roberts, Margaret E. (Princeton, New Jersey Princeton University Press, 2018)
As authoritarian governments around the world develop sophisticated technologies for controlling information, many observers have predicted that these controls would be ineffective because they are easily thwarted and evaded by savvy Internet users. In Censored, Margaret Roberts demonstrates that even censorship that is easy to circumvent can still be enormously effective. Taking advantage of digital data harvested from the Chinese Internet and leaks from China's Propaganda Department, this important book sheds light on how and when censorship influences the Chinese public. Roberts finds that much of censorship in China works not by making information impossible to access but by requiring those seeking information to spend extra time and money for access. By inconveniencing users, censorship diverts the attention of citizens and powerfully shapes the spread of information. When Internet users notice blatant censorship, they are willing to compensate for better access. But subtler censorship, such as burying search results or introducing distracting information on the web, is more effective because users are less aware of it. Roberts challenges the conventional wisdom that online censorship is undermined when it is incomplete and shows instead how censorship's porous nature is used strategically to divide the public. -- Inside jacket flap.
Introduction. The puzzle of porous censorship ; Distraction and diversion ; Implications and challenges to conventional wisdom ; The plan of the book -- A theory of censorship. Why do governments censor? ; Citizens are rationally ignorant ; Traditional media care about story costs ; Citizens exchange low-cost information through social media ; What is censorship? ; The mechanisms of censorship ; Fear ; Friction ; Flooding ; Conclusion -- Censorship in China. Modern history of information control in China ; Censorship of the Chinese Internet -- Reactions to experience with censorship. China's targeted censorship strategy ; The costs of observable censorship ; Matched comparison of censored and uncensored social media users ; An experimental study of consumers of social media ; Conclusion -- The powerful influence of information friction. The effects of content filtering on the spread of information ; Structural frictions and the Great Firewall ; When does friction fail? ; Conclusion -- Information flooding : coordination as censorship. What effect can propaganda have in the digital age? ; Flooding in China ; Detection of information flooding in newspapers and online media ; The influence of flooding on the spread of information ; Conclusion -- Implications for a digital world. Why porous censorship matters ; Authoritarian resilience ; Implications for free speech in democracies ; A call for future research -- Appendix. Description of the China Urban Governance Survey ; Words related to censorship, mutual information ; Tibet self-immolations negative binomial model.
Includes bibliographical references (pages 243-259) and index.
Keywords: Censorship -- China; Freedom of information -- China; Internet -- Censorship -- China; Social media -- Censorship -- China